2020
DOI: 10.1016/j.ijbiomac.2020.08.082
|View full text |Cite
|
Sign up to set email alerts
|

Balancing the decomposable behavior and wet tensile mechanical property of cellulose-based wet wipe substrates by the aqueous adhesive

Abstract: With the current global outbreak of novel coronaviruses, the fabrication of decomposable wet wipe with sufficient wet strength to meet daily use is promising but still challenging, especially when renewable cellulose was employed. In this work, a decomposable cellulose-based wet wipe substrate is demonstrated by introducing a synthetic N-vinyl pyrrolidone-glycidyl methacrylate (NVP-GMA) adhesive on the cellulose surface. Experimental results reveal that the NVP-GMA adhesive not only significantly facilitates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…With the recent outbreak of COVID-19 pandemic worldwide, the fear of infection has increased dramatically, and therefore the demands for medical nonwoven masks and disinfection wipes have rapidly increased too [ 1 ]. The severity of coronavirus infection can cause pneumonia, sever acute respiratory syndrome (SARS), and even can leads to death.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the recent outbreak of COVID-19 pandemic worldwide, the fear of infection has increased dramatically, and therefore the demands for medical nonwoven masks and disinfection wipes have rapidly increased too [ 1 ]. The severity of coronavirus infection can cause pneumonia, sever acute respiratory syndrome (SARS), and even can leads to death.…”
Section: Introductionmentioning
confidence: 99%
“…So, this pandemic had resulted in a crucial socio-economic impact globally [ 2 ]. It was stated that in 2019, the global medical nonwovens market value will reach 1.28 billion dollars and will continue to grow at an annual rate of 1.28 billion dollars and will continue to grow at annual rate of 4.6% and it is estimated to reach a market size of 1.61 size of billion dollars by 2024 [ 1 ]. Disinfection wipes known also as pre-impregnated disinfecting wipes, they are widely used for various applications particularly in critical areas in hospitals and healthcare centers for the decontamination of medical devices and high-touch environmental surfaces due to their effective performance [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Potential outcomes of this work indicated that cellulose based thin flms can be a suitable alternative for plastic packaging if processed further [60]. Along with that, they can be used in herbal medicine related to skin diseases due to their antimicrobial efcacy, as wet wipes [61], edible packaging [62], and wound healing tendency [47], because they are obtained from natural resources [63], such as fruit peels [64], leaves [65,66], and biodegradable in nature [67]. So, they can have various potential applications in various healthcare systems [68], energy storage devices [69], and wastewater treatment [70].…”
Section: Ftir Analysismentioning
confidence: 93%
“…22,23 In order to address the aforementioned challenges, researchers have made significant efforts to find alternatives to traditional wet strength resin PAE. Both synthetic 24 and natural polymers 9 with linear or less branched structures have been developed as wet strength agents. Synthetic wet strength agents, primarily polymer-based, include polyacrylamide and polyethylenimine.…”
Section: Introductionmentioning
confidence: 99%